2020
DOI: 10.1186/s13223-020-0405-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of levels of asthma control among adult patients with asthma at Chitungwiza Central Hospital, Zimbabwe

Abstract: Background: The management of the reversible airways obstruction forms the cornerstone of quality asthma management. The aim of this study was to assess the level of control for asthma in adult patients, using a cross sectional study design. The assessment of control for asthma was based on the ACQ. Methods: We conducted a cross-sectional study to measure the level of control for asthma among patients with asthma who volunteered and were reporting to Chitungwiza Central Hospital. We interviewed and conducted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…Our meta-analysis study result was higher than the studies conducted in Ethiopia [20,24], Canada [25], Zimbabwe [25], and Morocco [26]. This might be due to differences in sample size and study design.…”
Section: Discussioncontrasting
confidence: 77%
“…Our meta-analysis study result was higher than the studies conducted in Ethiopia [20,24], Canada [25], Zimbabwe [25], and Morocco [26]. This might be due to differences in sample size and study design.…”
Section: Discussioncontrasting
confidence: 77%
“…We also observed proximity to healthcare facilities from the patient’s residence increased the likelihood of seeking care from a given health facility (Figure 3). Similar observations were confirmed by Ndarukwa et al (2020) studying HSB of adult patients with asthma at a public hospital in Zimbabwe. Second, we investigated the means of transportation used by patients to arrive at healthcare facilities.…”
Section: Resultssupporting
confidence: 70%
“…We briefly discuss previous work analyzing patient HSB in both international and Indian contexts. Previous studies primarily considered assessing behavior of patients with respect to diseases such as cancer (Habtu et al 2018; Mubin et al 2021), tuberculosis (Kaur et al 2013; Thomas et al 2021), oral diseases (Deolia et al 2020), asthma (Ndarukwa et al 2020), ante- and prenatal care (Shahabuddin et al 2017; Matsubara et al 2019), mental illness (Srivastava et al 2021), non-communicable diseases (Rasul et al 2019), diabetes (Low et al 2016), whiplash injury (Tenenbaum et al 2017), and HIV (Lafort et al 2016) among others. HSB was analyzed with respect to patient-related attributes such as gender (Thompson et al 2016; Kapoor et al 2019; Rana et al 2020) or a specific age group (Cho et al 2008; Shrivastava 2014; Srivastava et al 2021), rurality/urbanity (Nemet & Bailey, 2000; Herberholz & Phuntsho, 2018; Liu et al 2018; Liu et al 2019), marital status (Shahabuddin et al 2017), and socioeconomic status (Matsubara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an analysis of archival 2017-2018 courier data in Malawi revealed that 30.08% (24,256/80,648) of the courier visits to clinics were empty trips. This not only results in inefficient use of limited resources but also contributes to delays in receiving critical test results [ 5 ], which in turn leads to poor health-seeking behavior among the population [ 6 ] and can contribute to increased mortality rates [ 7 ].…”
Section: Introductionmentioning
confidence: 99%